Real-time wireless monitoring for three phase motors in industry: a cost-effective solution using IoT - Khan, Talha Ahmed; Shaikh, Faraz Ahmed; Khan, Sheroz; Siddiqui, M Farhan (IEEE, 2019)
In recent days modern environment industries are facing rapid flourishing for performance capabilities and their requirements for corporate clients and industrial sector. Internet of Things (IoT) is an innovative and rapidly growing field for automation and evaluation in networks, Artificial Intelligence, data sensing, data mining, and big data. These systems have a great tendency to monitor and control different process used in industries. IoT systems have been implemented and have applications in different industries due to their cost-effectiveness and flexibility In this paper we have developed a system which includes real-time monitoring of current reading of three-phase motor through a wireless network. With the help of this system, data can be saved and monitored and then transmitted to cloud storage. This system contains Arduino-UNO board, ACS-712 current sensor, ESP-8266 Wi-Fi module which sends information to an IoT API service THING-SPEAK that behave like a cloud for various sensors to monitor data. The proposed system was successfully deployed in Aisha Steel Mills, Karachi, Pakistan.